Conservation of the glycoprotein B homologs of the Kaposi’s sarcoma-associated herpesvirus (KSHV/HHV8) and Old World primate rhadinoviruses of chimpanzees and macaques - Bruce, A. Gregory (Virology, 2016)
The envelope-associated glycoprotein B (gB) is highly conserved within the Herpesviridae and plays a critical role in viral entry. We analyzed the evolutionary conservation of sequence and structural motifs within the Kaposi’s sarcoma-associated herpesvirus (KSHV) gB and homologs of Old World primate rhadinoviruses belonging to the distinct RV1 and RV2 rhadinovirus lineages. In addition to gB homologs of rhadinoviruses infecting the pig-tailed and rhesus macaques, we cloned and sequenced gB homologs of RV1 and RV2 rhadinoviruses infecting chimpanzees. A structural model of the KSHV gB was determined, and functional motifs and sequence variants were mapped to the model structure. Conserved domains and motifs were identified, including an “RGD” motif that plays a critical role in KSHV binding and entry through the cellular integrin αVβ3. The RGD motif was only detected in RV1 rhadinoviruses suggesting an important difference in cell tropism between the two rhadinovirus lineages.